Mental imagery in link system - Campos García, Alfredo (1998)
Four experiments were carried out to explore the intluence of imaging capacity and image type (normal or bizarre) on immediate and delayed recall of word lists. Experiments 1 and 2 studied immediate serial recall of 16- and 28-item word lists, and experiments 3 and 4 studied serial recall of 16- and 28- item word lists one week after their presentation. Imaging capacity, as measured by the Space Scale of the Primary Mental Abilities Test, affected immediate recall of long lists. Image type affected immediate recall of short lists. In four experiments there was a significant difference between the performance of subjects who used mental imagery for recall and those who did not.